Impact of Health Promotion Interventions on Early Childhood Caries Prevention in Children Aged 2–5 Years Receiving Dental Treatment Under General Anesthesia - Razeghi, Samaneh; Amiri, Pardis; Mohebbi, Simin Z.; Kharazifard, Mohammad J. (Frontiers in Public Health, 2020)
Aim: This study was conducted to evaluate the impact of health promotion interventions on early childhood caries prevention in 2–5 year-olds receiving dental treatment under general anesthesia. Materials and Methods: Thirty-seven mother-child couples presenting to the clinic of the Dental School of Tehran University of Medical Sciences for treatment under general anesthesia were randomly divided to two groups: 19 couples in the pamphlet and fluoride varnish four times a year, and 18 couples in the pamphlet plus six phone call reminders and fluoride varnish four times a year. A standard questionnaire on demographics and children oral health-related practice of parents was completed by respondents. On children's oral examination, the Simplified Oral Hygiene Index (OHI-S), dmft, and the presence of new white spot lesions (WS) were recorded in both phases. At the final stage, Early Childhood Oral Health Impact Scale (ECOHIS) was completed by parents. The length of follow-up was 24 months. Results: In both groups, there was an increase in the number of mothers who knew how to brush their children's teeth as well as the number of mothers who brushed their children's teeth (P < 0.05). In the reminder group, an improvement occurred in the mothers' perception of their perceived ability to make their children brush their teeth twice a day (P = 0.03). Clinical examination revealed a significant decrease in the OHI-S (from 1.9 ± 0.8 to 1.15 ± 0.5) and the number of WS (from 8.5 ± 5.5 to 0.08 ± 0.5) in both groups on the follow-up visit. The mean dmft was 11.0 ± 4.0 with a mean d component of 10.56 ± 4 at the baseline, which decreased significantly to 1.44 ± 1.96 after dental treatment. No significant increase was seen in new caries in the intervention groups. There was no significant difference in the ECOHIS score between the two groups. Conclusion: The similar impact of both interventions suggests the possibility of applying the simpler one, i.e., the educational pamphlet, fluoride varnish and frequent follow-ups. However, in the reminder group, the mothers' perception of their perceived ability to make children brush their teeth twice a day was improved.